P032: Video-based learning modules as an adjunct for teaching emergency medicine procedural skills. (May 2019) - Dong, J.; Agarwal, S.; Wojtowicz, J.; Hanel, E.
Abstract : Innovation Concept : Competence in procedural skills is vital within the emergency department. Challenging procedures such as cricothyroidotomy are difficult to master as they are rare and hard to train for. Additionally, common procedures such as chest tube insertions require practice to become sufficiently competent. Opportunities to hone these skills are essential in residency training. This project aimed to create instructional video modules for specific emergency medicine (EM) procedures and to gauge its utility as an adjunctive resource for procedural learning in the EM residency curriculum.Methods : Tutorial videos for clamshell thoracotomy, cricothyroidotomy, and chest tube insertion were filmed within a cadaver lab with step-by-step instructions. The footage was edited and overlaid with a prepared audio narration using Camtasia®/Apple® Video Editing software. These videos were embedded within modules that included foundational knowledge relevant to the procedures including anatomy, physiology and pathophysiology. The modules were peer-edited by licensed EM staff physicians and distributed to EM residents and staff physicians for analysis. Qualitative and quantitative analysis relied upon participants' answers to questions and a Modified Task Value Scale (measures the value of a module for overall learning), respectively.Curriculum, Tool or Material : Ten participants were included in the analysis, including EM residents (n = 6) and staff emergency physicians (n = 4). Qualitative feedback suggested that positive aspects of the modules included visuals, content, narration, and review of anatomy. Negative aspects included the lack of indications for procedures, technical details, real patient examples, and a speed up function. Quantitative feedback resulted in scores of 4 and above out of 5 (1 = lowest value, 5 = highest value) on the Motivated Task Value Scale across all aspects for all the modules. Furthermore, analysis revealed an average score of 3.9/5 for inclination to access more modules such as these, and a score of 4.4/5 for overall perception of the modules.Conclusion : Participants found the video modules valuable to their learning, both qualitatively and quantitatively. This study was limited by a small sample size of modules and a low number of participants. Furthermore, a more detailed analysis with further measures, including self-efficacy and self-confidence, would yield more comprehensive conclusions. However, video modules provide an effective and easily accessible adjunctive tool to acquire skill and confidence with EM procedures, for medical learners and staff physicians.